Good Corporate Governance and Earning Management Practices: An Indonesian Cases - Werner R. Murhadi (Universitas Kristen Maranatha, 2011)
This research is done for the purpose of finding out the effect of Good Governance practice can reduce earnings management practice done by company. This research uses companies registered in manufacture sector in Indonesia Stock Exchange Observation period 2005-2007 as samples. Last sample used in this research is 384 years of observation. This research uses OLS method. The result allows that only two variables have significant effect to Earning Management practice which is CEO Duality an controlling stakeholder existence. Other independent variable such as independent commissioner and audit committee and also shareholder coalition outside the controlling shareholder don't have any effort to earning management practice in the company. COntrolvariable like covergence analyst and debt don't have anny effect either, to earning management practice existence.Keywords: good corporate governance, earning management, coverage analyst, debt.